Comparative Kinematic Analysis of Hurdle Clearance Technique in Dogs: A Preliminary Report - Francisco Miró; Patricia López; Jose Manuel Vilar; Alfonso M. Galisteo; Joaquín Vivo; Juan L. Garrido-Castro; Luna Gutierrez-Cepeda (Animals, 2020)
Although the jumping characteristics of agility dogs have been examined in recent years, there is currently a lack of data related to the suspension phase. The purpose of the present study was to investigate the biomechanics of the suspension phase of the agility jump and to analyze the kinematic differences in dogs with different jumping abilities. Two groups of dogs of the same height category (large dogs) competing at different skill levels and assessed as excellent jumpers (n = 4) and less-skilled jumpers (n = 3), respectively, were analyzed and statistically compared. Excellent jumpers showed longer and faster jumps with flatter jump trajectories than less-skilled jumpers. In less-skilled jumpers, the distance in front of the hurdle was notably greater than the distance behind it, while the difference between these two distances was less in excellent jumpers. Length and duration of the jump, maximal height of the jumping trajectory, take-off and landing distances to the hurdle, time of occurrence of maximal jump height, and time of change in back orientation essentially defines the suspension phase of the agility jump. This study presents preliminary evidence that the kinematic characteristics of hurdle clearance are different in excellent jumper dogs and in less-skilled jumper dogs.